Perencanaan Tempat Penyimpanan Sementara (TPS) Limbah B3 (Studi Kasus: Kantor PT Pertamina Jagir, Surabaya) - Fitri Alya Tampubolon; Firra Rosariawari (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Hazardous and Toxic Waste (B3) can cause pollution and environmental damage if directly discharged into the environment. To avoid the impact caused by B3 waste, an integrated and sustainable management system is needed. Hazardous and toxic waste generated by PT Pertamina Jagir office, Surabaya is still not managed according to applicable regulations. Hazardous and toxic waste management efforts are one of the efforts in the implementation of environmentally sound sustainable development. One of the efforts that can be done to overcome the waste problem at the PT Pertamina Jagir office, Surabaya is to carry out Planning and Management of Temporary Storage Areas (TPS) hazardous and toxic waste. This planning consists of 2 rooms, namely, a room for medical waste and a room for solid and liquid waste. The building area of the hazardous and toxic waste TPS is 18,10 m2 with details of 4,96 m x 3,65 m.